(untitled) (Anclajes, 2014)
Literary criticism on Ricardo Piglia´s narrative has often been oriented to micro-analyses, as if a permanent focus on minimal features was required: a sentence, a phrase, a quote. This leads to a further problem: the difficulty in envisaging a macro approach and systematization of the originality of Piglia´s narrative process. Thus, this paper intends to provide a broader view in an attempt to identify four recurrent rhetorical devices in his work: understatement, paradox, ellipsis and synechdoque, in relation to some literary genres (Bildungsroman,detective fiction andparanoidfiction).